How personality moderates the relationships between childhood environment, flow metacognitions, and creative ideational behavior: A preliminary study. (June 2022) - Zaeske, Lauren M.; Long, Haiying; Kahnke, Susanna A.; Kerr, Barbara A.
Highlights: High neuroticism interacted with childhood experience to predict flow metacognitions. Openness to experience significantly predicted creative variables Four of five Big Five personality factors were not significant moderators Abstract: There seems to be conflicting research findings about the role that personality and childhood environment play in predicting creativity. This study aims to fill this gap and explore through moderation analysis how personality, childhood environment, and their interaction affect two constructs that impact creativity outcomes: flow metacognitions and creative ideational behaviors. A sample of 59 adolescents from the midwestern region of the United States who were identified as creative through a profiling approach participated in the study. Results indicated that neuroticism significantly moderated the relationship between childhood environment and flow metacognitions. Openness to experience significantly predicted belief that flow fosters achievement and creative ideational behaviors, but it did not significantly moderate any proposed relationships. The significance of the findings to creativity is discussed.